A framework for eHealth readiness of dietitians. (July 2018) - Maunder, Kirsty; Walton, Karen; Williams, Peter; Ferguson, Maree; Beck, Eleanor
Highlights: No eHealth readiness frameworks exist for allied health professionals. Dietitian eHealth readiness themes: access, standards, attitude, aptitude, advocacy. An inductively developedF ramework fore HealthR eadiness ofD ietitians (FeRD). A model to examine, measure and drive strategies to prepare dietitians for eHealth. Further research may determine the FeRD is relevant to other allied health. Abstract: Aim: To develop a framework for assessing the eHealth readiness of dietitians. Methods: Using an inductive approach, this research was divided into three stages: 1. a systematic literature review to identify models or frameworks on eHealth readiness; 2. data synthesis to identify eHealth readiness themes and develop a framework; and 3. semi-structured interviews with Australian nutrition informatics experts to gain consensus and validate the framework. Results: Two hundred and forty one unique citations were identified, of which twenty four met the research criteria and were included in the review and subsequent synthesis. Common eHealth readiness themes or dimensions were extracted from the literature, and five key dimensions were identified that were relevant to dietitian eHealth readiness: access, standards, attitude, aptitude and advocacy. A framework diagram was designed and discussed during semi-structured interviews with ten nutrition informatics experts to inform the final framework. The result of this research was an inductively developedF ramework fore HealthR eadiness ofD ietitians (FeRD). Discussion: The FeRD builds on existing theories and models, and provides a conceptual model for developing eHealth readiness evaluation tools to examine, measure and drive strategies to better prepare dietitian professionals for eHealth.